Semiotic Analysis of Signifiers and Signifieds in Social Media Advertisements: Brand Identity and Consumer Perception: English (PANOPTICON: Journal of English Studies, 2025)
This study examines the role of signifiers and signifieds in product advertisements on social media, applying Ferdinand de Saussure’s semiotic theory to explore how visual and textual elements shape brand identity and consumer perception. Using a qualitative approach, this research analyzes advertisements from ten global brands, including Nike, Coca-Cola, Apple, Dove, McDonald's, Starbucks, L'Oréal, GoPro, Audi, and Rolex. Findings indicate that each brand strategically employs a combination of visual signifiers—such as logos, imagery, and colors—alongside verbal elements like slogans to convey deeper meanings associated with brand values, identity, and emotional appeal. The study concludes that the strategic use of semiotic elements in advertising enhances brand-consumer relationships and reinforces brand identity beyond the functional aspects of a product.